Psychoanalytic psychotherapy : a handbook - Elzer, Matthias; Gerlach, Alf (EFPP clinical monograph series., 2014)
The book gives the reader an introductory understanding of the psychoanalytic theory of the human mind, the psychic development, psychic conflicts, trauma, symptom formation, and dreams. Related to these theoretical aspects the book then introduces the fundamentals of psychoanalytic-oriented psychotherapy. The first part of this book deals with important technical aspects of the psychotherapeutic treatment such as the therapeutic relationship, the setting, the diagnosis, and the process of treatment. The second part explores the psychoanalytic understanding of specific clinical disorders, including neuroses and personality. A Basic Book of Psychoanalytic Psychotherapy will provide a complete overview from a psychoanalytical point of view of theoretical and clinical aspects of psychodynamic or psychoanalytic psychotherapy.